2001
DOI: 10.1080/00221300109598900
|View full text |Cite
|
Sign up to set email alerts
|

Item-Cued Directed Forgetting of Related Words and Pictures in Children and Adults: Selective Rehearsal Versus Cognitive Inhibition

Abstract: The main purpose of this study was to compare the relative importance of selective rehearsal and cognitive inhibition in accounting for developmental changes in the directed-forgetting paradigm developed by R. A. Bjork (1972). In two experiments, children in Grades 2 and 5 and college students were asked to remember some words or pictures and to forget others when items were categorically related. Their memory for both items and the associated remember or forget cues was then tested with recall and recognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 24 publications
1
11
1
Order By: Relevance
“…This typically leads to a DF effect, better memory for TBR than for TBF. The effect is apparent both in recall and recognition ( Basden and Basden, 1996 ) and has been shown for a variety of materials ( Lehman et al, 2001 ; Hourihan and Taylor, 2006 ; Hauswald and Kissler, 2008 ; Hourihan et al, 2009 ; Quinlan et al, 2010 ; Nowicka et al, 2011 ; Zwissler et al, 2011 ).…”
Section: Introductionmentioning
confidence: 83%
“…This typically leads to a DF effect, better memory for TBR than for TBF. The effect is apparent both in recall and recognition ( Basden and Basden, 1996 ) and has been shown for a variety of materials ( Lehman et al, 2001 ; Hourihan and Taylor, 2006 ; Hauswald and Kissler, 2008 ; Hourihan et al, 2009 ; Quinlan et al, 2010 ; Nowicka et al, 2011 ; Zwissler et al, 2011 ).…”
Section: Introductionmentioning
confidence: 83%
“…The results of the only investigation of the effects of related words on directed forgetting in children did not show any effect of cue combination, either in fifth graders or in college students (Lehman, McKinley-Pace, Leonard, Thompson, & Johns, 2001). Of interest, however, was the finding that children recognized more forget-cued words than did adults, a finding that is unique in the directed-forgetting literature.…”
mentioning
confidence: 96%
“…Although a significant directed forgetting effect occurred for words as well as line-drawings, the magnitude of the directed forgetting effect was smaller for line-drawings compared to words. Similarly, Hauswald and Kissler (2008) used complex pictures from the International Affective Picture System (IAPS; Lang, et al 2005) database in a standard item-method directed forgetting paradigm and found that the magnitude of the directed forgetting effect was smaller for complex IAPS pictures compared to line-drawings (e.g., Lehman, McKinley-Pace, Leonard, Thompson, & Johns, 2001). Together, these findings suggest that as the visual complexity of a stimulus increases, the magnitude of the directed forgetting effect decreases.…”
Section: Directed Forgettingmentioning
confidence: 99%